1998
DOI: 10.1038/2431
|View full text |Cite
|
Sign up to set email alerts
|

NRSF/REST is required in vivo for repression of multiple neuronal target genes during embryogenesis

Abstract: The neuron-restrictive silencer factor NRSF (also known as REST and XBR) can silence transcription from neuronal promoters in non-neuronal cell lines, but its function during normal development is unknown. In mice, a targeted mutation of Rest, the gene encoding NRSF, caused derepression of neuron-specific tubulin in a subset of non-neural tissues and embryonic lethality. Mosaic inhibition of NRSF in chicken embryos, using a dominant-negative form of NRSF, also caused derepression of neuronal tubulin, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
422
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 437 publications
(440 citation statements)
references
References 34 publications
16
422
0
2
Order By: Relevance
“…It is interesting to note that in this work, the β-tubulin III -YFP construct introduced into the mouse did not include the NRSE, The neuronal accumulation, as well as the lack of non-neuronal accumulation of YFP, provides strong evidence that the control of β-tubulin III expression is not solely dependent on NRSF (Dennis et al, 2002). One possible mechanism by which this may occur has been presented previously (Chen et al, 1998). A further comparison of the rat (Dennis et al, 2002) and mouse β-tubulin III promoters shows that both upstream regions possess similar classes of transcription factor binding sites including AP2, C/EB, E-box, and SP1 sites, although the precise locations upstream from the TATA box are often not identical (Dennis et al, 2002;Uittenbogaard and Chiaramello, 2002).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It is interesting to note that in this work, the β-tubulin III -YFP construct introduced into the mouse did not include the NRSE, The neuronal accumulation, as well as the lack of non-neuronal accumulation of YFP, provides strong evidence that the control of β-tubulin III expression is not solely dependent on NRSF (Dennis et al, 2002). One possible mechanism by which this may occur has been presented previously (Chen et al, 1998). A further comparison of the rat (Dennis et al, 2002) and mouse β-tubulin III promoters shows that both upstream regions possess similar classes of transcription factor binding sites including AP2, C/EB, E-box, and SP1 sites, although the precise locations upstream from the TATA box are often not identical (Dennis et al, 2002;Uittenbogaard and Chiaramello, 2002).…”
Section: Discussionmentioning
confidence: 70%
“…The mouse β-tubulin III NRSE is located in the first intron (Schoenherr et al, 1996). Anderson and colleagues (Chen et al, 1998;Schoenherr and Anderson, 1995;Schoenherr et al, 1996) have shown that the β-tubulin III gene is regulated in part by the NRSF. It is interesting to note that in this work, the β-tubulin III -YFP construct introduced into the mouse did not include the NRSE, The neuronal accumulation, as well as the lack of non-neuronal accumulation of YFP, provides strong evidence that the control of β-tubulin III expression is not solely dependent on NRSF (Dennis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Repressor element 1 (RE-1) silencing transcription factor/neuron restrictive silencing factor (REST/NRSF) is a zinc finger protein that triggers epigenetic silencing of neuronal genes . In mice lacking REST/ NRSF, the neural-specific gene ␤III-tubulin is expressed in some non-neural tissues, but many cell types are unaffected (Chen et al, 1998). However the mice die at E11.5, precluding insight into the roles for REST in nervous system development.…”
Section: Lineage Restriction Rest/nrsf Activities Govern Neuronal Fatmentioning
confidence: 99%
“…This is especially evident in studies of stem cells where much of the cells chromatin appears to carry a "bivalent" or mixed signature comprising both "active" and repressed' marks (Azuara et al, 2006;Bernstein et al, 2006). Also, remember that in the RESTϪ/Ϫ embryo, very few target genes were precociously activated (Chen et al, 1998). This of course could be due to absence of appropriate activators.…”
Section: Do You Think That Many Developmental Decisions Are Epigenetimentioning
confidence: 99%
“…For example, BAF family complex members Brg1, BAF57, and BAF170 have been shown to associate as a larger complex with the neural restrictive silencing factor (NRSF/REST) and its co-repressors (eg, Sin3A, CoREST, and MeCP2) in non-neuronal cells (Ooi et al, 2006). NRSF/REST expression is restricted to nonneuronal cells, and as a zinc finger domain containing transcription factor, binds to target motifs (RE1) and represses transcription of neuronal specific genes through association with its co-repressors (Chong et al, 1995;Chen et al, 1998;Lunyak et al, 2002;Ballas et al, 2005). Recent evidence demonstrates that the repressive activity of NRSF/ REST requires a functional bromodomain interaction with Brg1, whereby Brg1 is recruited to RE1 sites to synergistically control the expression of neuronal gene programs in non-neuronal cells (Ooi et al, 2006).…”
Section: Impact Of Chromatin Remodeling On Neural Developmentmentioning
confidence: 99%